On the achromatic number of P(α, Kn), P(α, K1,n) and P(α, Km,n) - Mammana, Maria Flavia (Utilitas Mathematica, 2002)
The achromatic number of a graph was introduced by F. Harary and S. Hedetniemi in 1970. We give some results concerning the achromatic number for permutation graphs G, when G is Kn, K1,n or Km,n.